Microbiota-derived proteins synergize with IL-23 to drive IL22 production in model type 3 innate lymphoid cells. - Yanling Wang; David S J Allan; Andrew T Gewirtz (PLoS ONE)
Microbiota-induced production of IL-22 by type 3 innate lymphoid cells (ILC3) plays an important role in maintaining intestinal health. Such IL-22 production is driven, in part, by IL-23 produced by gut myeloid cells that have sensed select microbial-derived mediators. The extent to which ILC3 can directly respond to microbial metabolites via IL-22 production is less clear, in part due to the difficulty of isolating and maintaining sufficient numbers of viable ILC3 ex vivo. Hence, we, herein, examined the response of the ILC3 cell line, MNK-3, to microbial metabolites in vitro. We observed that fecal supernatants (FS), by themselves, elicited modest levels of IL-22 and synergized with IL-23 to drive robust IL-22 production assayed by qRT-PCR and ELISA. The IL-22 synergistic activity of FS was not mimicked by an array of candidate microbial metabolites but could be attributed to bacterial proteins. Examining how MNK3 cells exposed to IL-23, FS, both, or neither via RNA-seq and immunoblotting indicated that FS activated MNK-3 cells in a distinct pattern from IL-23: FS activates p-38 MAPK while IL-23 activates STAT3 signaling pathways. Collectively, these studies indicate ILC3 sensing of microbiota proteins promotes IL-22 production suggesting the possibility of manipulating microbiota to increase IL-22 without risk of IL-23-mediated chronic inflammatory diseases.